Transformational Leadership and Employee Performance: Mediation of Organizational Citizenship Behavior - Aristana, I Nengah; Adhika, I Nyoman Resa; Rihayana, I Gede; Salain, Putu Pradiva Putra (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to measure transformational leadership and employee performance mediated by organizational citizenship behavior. This research uses a quantitative approach, data was collected from 210 employees of small and medium enterprises. Data were analyzed using Smart PLS 3.2.9. The research results show that transformational leadership does not affect employee performance. Meanwhile, transformational leadership contributes positively to organizational citizenship behavior, and organizational citizenship behavior also shows a positive impact on employee performance. Lastly, organizational citizenship behavior is proven to mediate transformational leadership about employee performance. Limitations of this research that can be stated include using a self-assessment report which allows for high subjectivity when filling out the questionnaire. The research only focuses on small and medium export businesses, so the research results tend to be less generalizable.